PALEOCEANOGRAPHIC CONDITIONS AT THE BASE OF THE PLIOCENE IN THE SOUTHERN MEDITERRANEAN BASIN (Rivista italiana di Paleontologia e Stratigrafia, 1997)
Detailed quantitative analyses of the benthic foraminiferal assemblage from the base of the Pliocene sections (M Pl 1 biozone) at Eraclea Minoa and the Capo Rossello area (southern Sicily) documented fluctuating paleoecological conditions indicative of a dysaerobic bottom water environment. In particular, we identify the Uvigerina pygmaea-peregrina Event, which in the area studied covers the upper part of the M Pl 1 biozone. According to the integrated calcareous plankton biostratigraphy and to cyclostratigraphy based on fluctuations in the relative abundance of fauna in the planktonic foraminiferal assemblage, the base of the Uvigerina pygmaea-peregrina Event coincides with cycle 6a and its top coincides with cycle 10 in the Sicilian sections.A similar temporal correlation is seen in the Tyrrhenian basin (ODP Site 652). On the contrary, the Uvigerina pygmaea-peregrina Event covers a longer time interval in the Jonian basin, where it is recognizable from cycle 4 to cycle 12. The Uvigerina pygmaea-peregrina Event is time equivalent with an interval characterized by cyclically repeated sapropels in the eastern Mediterranean basin. As a matter of fact, 10 sapropels are present in the deep-sea sediments (ODP Site 969) and 10 Uvigerina pygmaea-peregrina peaks are present in the Roccella Ionica - Capo Spartivento composite section in the M Pl 1- lowest M Pl 2 biozones. The diachronous termination of the Uvigerina pygmaea-peregrina Event may indicate that well-oxygenated bottom conditions were established earlier in the western than in the eastern Mediterranean basin. Both the sapropels interval in the eastern Mediterranean and low-oxygen bottom conditions in the Jonian basin occurred during a time interval which straddles a minimum of eccentricity in the astronomical record.